2004
DOI: 10.1080/00016480410022525
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glucocorticoid on Upregulation of Histamine H1Receptor mRNA in Nasal Mucosa of Rats Sensitized by Exposure to Toluene Diisocyanate

Abstract: As shown in TDI-sensitized rats, our findings suggest that the upregulation of H1R in the nasal mucosa is one of the mechanisms responsible for nasal hypersensitivity behavior and nasal hypersensitivity to histamine and that the therapeutic effects of dexamethasone are, in part, due to its inhibitory action on the upregulation of H1R.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 20 publications
3
47
0
Order By: Relevance
“…This expression was maximal after 4 h of TDI provocation (12). Pretreatment with suplatast significantly reduced H1R expression in the nasal mucosa of the TDI-sensitized rats (Fig.…”
Section: Effect Of Suplatast On Tdi-induced Increases In H1r Mrna Expmentioning
confidence: 96%
See 3 more Smart Citations
“…This expression was maximal after 4 h of TDI provocation (12). Pretreatment with suplatast significantly reduced H1R expression in the nasal mucosa of the TDI-sensitized rats (Fig.…”
Section: Effect Of Suplatast On Tdi-induced Increases In H1r Mrna Expmentioning
confidence: 96%
“…Although AR, defined as an IgE-mediated disease, could be different from TDI-induced, non-IgE-mediated rhinitis, nasal allergic-like symptoms induced by TDI are similar to those observed in AR patients (38,39). Additionally, TDI-sensitized rats also display many of the characteristic features of AR in humans, including infiltration of eosinophils and mast cells (40), increase in the level of cytokines (8,(41)(42)(43), elevation of H1R mRNA and protein level (12), increase in the HDC mRNA level, HDC activity, and histamine content (13), even though histamine release was triggered by neuropeptide, but not IgE, in TDI-sensitized animals. Furthermore, the expression of IL-4 and IL-5 mRNAs was also up-regulated in the nasal mucosa of TDI-sensitized rats after provocation with TDI (16,17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The strength of H1R signaling depends on the H1R expression level (8). Our recent studies have demonstrated that the level of H1R gene expression is strongly correlated with the severity of allergic symptoms in model rats and patients with pollinosis (9,10), and compounds that suppress H1R gene up-regulation alleviate allergic symptoms (11)(12)(13)(14)(15)(16). These findings suggest that the H1R gene is an allergy-sensitive gene, i.e.…”
mentioning
confidence: 90%